Strategic intervention materials-based instruction on disaster literacy for technology students using the ADDIE model - Mutya, Romel C.; Tondo, Reynaldo C.; Aragon, Kaye Marion P.; Tablate, Donna Jean C.; Bonotan, Amelia M. (Frontiers in Education, 2025)
Disaster literacy among technology students is crucial for effective disaster management, especially in the Philippines, a country prone to natural hazards. This study evaluated the effectiveness of strategic intervention materials (SIM)-based instruction, employing the ADDIE model, in enhancing disaster literacy among technology students. The study used an explanatory sequential research design, integrating an experimental one-group pretest-posttest quantitative analysis with an experiential, phenomenological qualitative approach. Thirty second-year technology students in an environmental science course were recruited using the fishbowl randomization method. The SIM was assessed using a set of criteria, including content, format, presentation, and information accuracy. All five modules exceeded the minimum required standards. Students were engaged in SIM-based instruction, focusing on disaster risk reduction management. Pretest-posttest data revealed statistically significant improvement in student performance on disaster topics, with the overall mean score increasing from 18.97 to 39.50 (p < 0.001). Despite weak correlations among the domains, descriptive statistics and correlation analysis showed high student agreement in cognitive, affective, and psychomotor domains, indicating holistic learning gains. Qualitative findings further supported the quantitative results, highlighting that SIM based instruction enhanced student engagement, comprehension, and independent learning. However, some participants noted challenges. These insights emphasize the need for further refinement by incorporating contextual examples and multimodal content to cater to diverse learning preferences. SIM is an effective pedagogical tool for disaster literacy, promoting active engagement, improved academic performance, and preparedness behaviors among students.